Neural Wiener Based MPC(NWMPC) for MTBE Catalytic Distillation (Creators without family name connot save) - Sudibyo, S.; Murat, M.N.; Aziz, N. (2013)
Reactive distillation of MTBE has strong interaction between the variables and is highly nonlinear process. Here, nonlinear MPC was proposed to tackle the nonlinearity and the interaction in controlling tray temperature of MTBE reactive distillation. To improve the performance of the MPC, advanced nonlinear block oriented model known as Neural Wiener.